Diverse dietary practices across the Early Bronze Age ‘Kura-Araxes culture’ in the South Caucasus - Manoukian, Nyree; Whelton, Helen L.; Dunne, Julie; Badalyan, Ruben; Smith, Adam T.; Simonyan, Hakob; Rothman, Mitchell S.; Bobokhyan, Arsen; Hovsepyan, Roman; Avetisyan, Pavel; Evershed, Richard P.; Pollard, A. Mark (PLOS ONE, 2022)
The Kura-Araxes (KA) cultural phenomenon (dated to the Early Bronze Age, c. 3500/3350-2500 BCE) is primarily characterised by the emergence of a homogeneous pottery style and a uniform ‘material culture package’ in settlements across the South Caucasus, as well as territories extending to the Ancient Near East and the Levant. It has been argued that KA societies practised pastoralism, despite a lack of direct examination of dietary and culinary practices in this region. Here, we report the first analyses of absorbed lipid residues from KA pottery to both determine the organic products produced and consumed and to reconstruct subsistence practices. Our results provide compelling evidence for a diversified diet across KA settlements in Armenia, comprising a mixed economy of meat and plant processing, aquatic fats and dairying. The preservation of diagnostic plant lipid biomarkers, notably long-chain fatty acids (C20 to C28) and n-alkanes (C23 to C33) has enabled the identification of the earliest processing of plants in pottery of the region. These findings suggest that KA settlements were agropastoral exploiting local resources. Results demonstrate the significance of applying biomolecular methods for examining dietary inferences in the South Caucasus region.